Comparing eye movements during mathematical word problem solving in Chinese and German - Strohmaier, Anselm R.; Schiepe-Tiska, Anja; Chang, Yu Ping; Müller, Fabian; Lin, Fou Lai; Reiss, Kristina M. (ZDM - International Journal on Mathematics Education, 2020)
Language plays an important role in word problem solving. Accordingly, the language in which a word problem is presented could affect its solution process. In particular, East-Asian, non-alphabetic languages are assumed to provide specific benefits for mathematics compared to Indo-European, alphabetic languages. By analyzing students’ eye movements in a cross-linguistic comparative study, we analyzed word problem solving processes in Chinese and German. 72 German and 67 Taiwanese undergraduate students solved PISA word problems in their own language. Results showed differences in eye movements of students, between the two languages. Moreover, independent cluster analyses revealed three clusters of reading patterns based on eye movements in both languages. Corresponding reading patterns emerged in both languages that were similarly and significantly associated with performance and motivational-affective variables. They explained more variance among students in these variables than between the languages alone. Our analyses show that eye movements of students during reading differ between the two languages, but very similar reading patterns exist in both languages. This result supports the assumption that the language alone is not a sufficient explanation for differences in students’ mathematical achievement, but that reading patterns are more strongly related to performance.
CRIS-Team Scopus Importer:2024-12-02
Keywords: Anxiety; Eye tracking; Flow; Reading; Self-concept; Word problem solving